The Concept of Contemporary Islamic Art: Bruneian Muslim Artists’ Perspective (LITPAM, 2025)
Contemporary Islamic art has emerged into a diverse and dynamic field, shaped by diverse cultural, social, and global influences. It also reflects the intersection of traditional Islamic aesthetics and the complexity of the modern world that are seen through artist’s creative expressions worldwide, including those from Brunei Darussalam, a Muslim-majority country in Southeast Asia. Artists, as actual practitioners and producers of creative works offer unique insights into their experiences, faith, and identities, enriching the multifaceted nature of contemporary Islamic art. Despite the importance of artists' involvement, for the past 50 years, studies that specifically document artists’ perspectives on the field have yet to be found. Therefore, this qualitative study attempts to address this gap by employing face-to-face, semi-structured interviews with 10 practising Bruneian Muslim artists. These artists-participants were selected for their unique experiences as Muslims, living in a Muslim-majority country that upholds the national philosophy, the Melayu Islam Beraja (abbreviated: MIB, translated as Malay Islamic Monarchy), which places Islam at the heart of its national identity. One of the key findings of this study is the diverse thematic exploration by Bruneian Muslim artists in defining contemporary Islamic art. This includes the aspect of time, practical approaches, Islamic presence, and recognised Islamic imagery. This study provides insights into how Bruneian Muslim artists define contemporary Islamic art, drawing on their experience to shape their understanding of the term. One implication of this study is the need to recognise the importance of artists' perspectives in the field, particularly through their lived experiences as practitioners.